THE ROLE OF HAPPINESS AND GRATITUDE ON SUBJECTIVE WELL-BEING AMONG STUDENTS - Majdi, M. Zuhdi Zainul; Mafirja, Sulma; Hj Sa’adah, Hj Sa’adah (Program Studi Bimbingan dan Konseling Universitas Tunas Pembangunan Surakarta, 2025)
In one's life, subjective well-being is essential. People take a variety of actions to feel comfortable in their lives. Happiness and gratitude can have an impact on one's subjective well-being. The goal of this study was to analyze the correlation among students' subjective well-being and their levels of happiness and gratitude. A quantitative method of explanatory correlation is used in this research. applying purposive sampling to sample the subject. There were 110 respondents in this survey. Three instruments the happiness scale, the gratitude scale, and the subjective well-being scale are used to collect data. SPSS was used for data analysis, namely multiple linear regression. The results of this study indicate that among college students, happiness and gratitude are significantly correlated with subjective well-being. The degree of students' subjective well-being increases with their level of happiness and gratitude.